Предмет: Алгебра,
автор: alonearno
Нужно упростить выражение. Задание на фото
Приложения:
Ответы
Автор ответа:
0
y² -9 =(y -3)(y +3)
3 -y = -(y -3)
y² +6y +9 =(y +3)²
(6 -(y+3)) /(y-3)(y+3) *(y+3)² /5 =(6 -y -3) *(y+3)² /(y-3)(y+3)*5 =3(y+3) /5(y -3) =0.6(y+3) /(y-3)
3 -y = -(y -3)
y² +6y +9 =(y +3)²
(6 -(y+3)) /(y-3)(y+3) *(y+3)² /5 =(6 -y -3) *(y+3)² /(y-3)(y+3)*5 =3(y+3) /5(y -3) =0.6(y+3) /(y-3)
Похожие вопросы
Предмет: Алгебра,
автор: Nastya23092007
Предмет: Русский язык,
автор: umnai44
Предмет: Қазақ тiлi,
автор: moldiramandykkyzy4
Предмет: Математика,
автор: DrObiopdjd
Предмет: Математика,
автор: наташа16